PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF PADA PEMBELAJARAN MATEMATIKA DI SMAN 10 MAKASSAR - Ahmad Rahmadani (Jurusan Pendidikan Teknik Elektro, 2025)
This study aims to investigate the effectiveness of the cooperative learning model in improving mathematics learning outcomes for students at SMAN 10 Makassar. A quasi-experimental research design was used with a pretest-posttest control group. The research sample included 120 students, with 60 students in the experimental group and 60 students in the control group. The experimental group was taught using cooperative learning, while the control group received conventional teaching. The results indicated that the experimental group achieved significantly higher posttest scores than the control group, demonstrating the positive impact of cooperative learning on students' mathematics performance. These findings suggest that cooperative learning can be an effective strategy to improve learning outcomes in mathematics education.